Evaluation of the effectiveness and efficiency of maser and digram methods in retrieving hadith documents / Mohd Yusof Mohd Zain - Mohd Zain, Mohd Yusof (2004)
Nowadays, Information Technology or IT has enabled information to be captured, transmitted, stored, retrieved, manipulated or displayed (Altar 1996) via a computer that is linked to the Internet. Not just that, mobile computer and telephone also can retrieve the information as the technology becomes more sophisticated from time to time. Information can be in many forms such as text, image or sound. Advance in information technology has made it possible for a wide range of text-based information to be searched and retrieved online, iocally or from remote hosts. More modem as well as historical or classical texts are scanned and stored in databases ready to be used for text retrieval systems. This has led to the increase in the number of new researchers into the area of information retrieval.